L’évaluation des réseaux de circulation en géographie quantitative - Jean-François Gleyze (Les Nouvelles de l’Archéologie, 2009)
Circulation networks are often implied in spatial phenomena, since they highlight displacements or relationships of places on territories. To analyse such phenomena, specifics tools are needed, in particular indicators coming from quantitative geography. Nevertheless, these indicators are often defined in thematic studies, and do not put forward a generic approach which would help to extract the intrinsic network properties and to draw up new indicators. Making this observation, we propose to develop a framework based on the study of the network structure, combining its topological, geometrical and metrical information. In focusing on the analysis of the paths offered by the network to carry out the relations between origin and destination nodes, this framework is relevant to highlight the network relational potentialities, i.e. its ability to link the different places on the territory. The process we use to draw up structural indicators helps not only to rebuild and reinterpret the traditional indicators supplied by quantitative geography (accessibility, betweenness), but also to build new indicators: in that respect, we explain this process for two indicators, describing on the one hand the network paths supply (paths number) and on the other hand the spatial range of relations in which the network nodes are implied (proximal radius). This process can be extended to analyse any property observable at the path level.